Prevalence of opportunistic bacterial infections (tuberculosis and pneumonia) among people with HIV in Ethiopia: Systematic review and meta-analysis - Aleka Aemiro; Abayeneh Girma; Getachew Alamnie; Demsew Beletew; Amere Genet (PLoS ONE, 2025)
Background Individuals with weakened immune systems, such as those living with Human Immunodeficiency Virus (HIV), are more vulnerable to opportunistic bacterial infections, which include tuberculosis and pneumonia. This systematic review and meta-analysis looked at the pooled prevalence of opportunistic bacterial infections among people living with HIV in different regions of Ethiopia. Methods By looking through open online databases, articles written in English were considered. Joanna Briggs Institute’s critical appraisal tool for prevalence study was used to check the quality of each article. Inverse variance (I 2 ), sensitivity analysis, funnel plot, and Egger’s regression tests were used to check heterogeneity and publication bias. Because of a high heterogeneity, a random-effects model was used to estimate the pooled prevalence of opportunistic bacterial infections among people living with HIV. Results About 18.06% (1824/9651) with (95% CI: 14.09–22.02) of the pooled population had opportunistic tuberculosis from 20 studies included, while from 16 included studies, the pneumonia infection was 11.64% (1040/8095/) with (95% CI: 8.45–14.83). Conclusion The prevalence of tuberculosis and pneumonia among people living with HIV in Ethiopia is high. Therefore, policymakers and health planners should put a great deal of emphasis on the implementation of relevant prevention and control measures. Registration The review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) with the registration number “CRD42024587645”, on September 17, 2024.